Postmodernizing the faith evangelical responses to the challenge of postmodernism - Erickson, Millard John, 1932- (Grand Rapids, MI Baker, 1998)
Includes bihbliographical references and index.
Keywords: Theology, doctrinal -- history -- 20th century; Postmodernism -- religious aspects; Evangelicalism -- response to postmodernism